Der Zweifel an Regierungsmaßnahmen als Sakrileg: römisches und kanonisches Recht bei der Ausbildung des päpstlichen und fürstlichen Absolutismus - Hageneder, Othmar (Zeitschrift für katholische Theologie, 1996)
The study offers examples of the tradition of the statement originated in Cod. 9. 29. 2(3) "Disputari de principali iudicio non oportet: sacrilegii enim instar est dubitare, an is dignus sit, quem elegerit imperator" in the Ius commune of the higher and later Middle Ages, from the Decretum Gratiani over decretists and decretalists to commentators and legists of the 14th and 15th century. The author also refers to the using by popes, especially Innocent III., to the acceptance of this argument within christianity during the 12th and 13th century, and to documents of civil law from the Assises of Ariano of King Roger II. of Sicily to various statements of absolutistic sovereigns and their functionaries of the 17th century. The theme could be given a deeper treatment.